The Role of Religion in Creating and Maintaining Ethnic Identity—The Example of the Kashubs in Poland - Monika Mazurek (Religions, 2021)
After 1945, the Republic of Poland appeared to be an ethnic monolith. However, this was (is) not the case for the Kashubians, who now live in northern Poland on the Baltic Sea. Presently, Kashubians do not have official status; they are not considered an ethnic or national minority. They create their own identity around language, origin, inhabited territory, and religion. The latter serves to maintain a sense of community—to legitimise the Kashubian language, the axial value of Kashubian ethnic identity. Kashubian religiosity is frequently emphasized in the public space. The objective of this article is to analyse the role of the Catholic religion in building the ethnic identity of Kashubians and legitimizing constructed traditions by the Kashubian-Pomeranian Association. The main purpose of the article is to show the process of ethnicisation of religions. This ethnic non-governmental organisation is aspiring to represent the Kashubian community in the public space in Poland. The results from studies conducted among members of this organization, which concern their views on the link between religious and secular events organised by the Association, will also be presented.